Pemanfaatan Limbah Kulit Singkong sebagai Kompos untuk Mendukung Pertanian Berkelanjutan di Desa Purwasari - Waskitho Aji Wijoyo; Muhammad Iqbal Nurulhaq; Edi Wiraguna (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2026)
Cassava is one of the strategic agricultural commodities in Indonesia, contributing significantly to national production, particularly in several major producing provinces. In addition to the challenge of declining harvested areas, cassava processing activities also generate agricultural waste that poses environmental risks. In Purwasari Village, Dramaga Subdistrict, Bogor Regency, household-scale cassava processing industries produce solid waste in the form of cassava peels, which are not optimally managed and are commonly discarded in the surrounding environment. This cassava waste has the potential to cause environmental pollution, unpleasant odours, and negative impacts on public health. One sustainable alternative for managing this cassava waste is the use of cassava peels as a raw material for composting. This study aimed to identify problems associated with cassava peel waste and to assess members of the Taruna Tani Millennial Farmer Group's interest in compost production using cassava peels. The research was conducted from December 2024 to June 2025 using a community-based assistance approach. Data was collected through interviews and questionnaires involving 20 respondents. The results showed that the main problems associated with cassava peel waste include waste accumulation, limited processing facilities, and low community awareness. Farmers’ interest in cassava peel composting was generally categorized as high, with an average score of 77%, although several indicators remained at a moderate level. Extension activities and hands-on demonstrations were proven to enhance farmers’ understanding, interest, and participation. With sustained educational support and adequate facilities, the use of cassava peel compost has strong potential to promote environmentally friendly, sustainable agricultural waste management.